Performing an Electrocardiogram Using the ECG Application on Apple Watch - Hssab, Dheyaa Rahi Tahir; Shabeb, Sara Halool Saad; Muhsen, Ayman Mu'ayyad Abdulrahman; Amigh, Mustafaa Ayad Jamigh; Jabr, Abrar Abdul Karim Taher; Fadel, Yousef Khaled Shamkhi (American Journal of Botany and Bioengineering, 2025)
The research project discusses the electrocardiogram and its usefulness in diagnosing various diseases that affect the heart and helps in finding the appropriate solution to these diseases using the application of the electrocardiogram on the Apple Watch, as well as the design and manufacture of a portable device to measure the electrocardiogram.